Análise polínica e química de amostras de pólen apícola monofloral de espécies da família Arecaceae - Alves, Rodolfo de França (2017)
The pollen grains are a protein resource collected by bees for feeding larvae and adults inside the hive. During this collection the bee Apis mellifera L. deposits salivary substances, rich in enzymes and vitamins that enrich the pollen grains nutritionally and this happens to be denominated bee pollen. This bee product can be classified as monofloral or multifloral, depending on the botanical composition of the samples. Palm trees are currently represented by 181 genera and approximately 2,600 species. In Brazil, there are 38 genera and about 270 species. They are plants with great potential in the production of monofloral bee pollen. However, this classification requires some care, for example, the counting method used, since it is necessary to take into account the volume of the pollen units during the process of quantification of the pollen types. It is important to emphasize the recent studies with bee pollen have shown that chemical composition became a priority, because the presence of important nutrients and bioactive compounds, such as antioxidants such as flavonoids, carotenoids promoted a higher consumption of bee pollen on the market and became Target of greater interest by science. In this context, the main goal of study was to perform a pollen and chemical analysis of the samples of bee pollen with monofloral indication of Arecaceae produced in the region of Baixo Sul of Bahia, to relate the frequency and pollen volume to confirm or refute the indication of beekeepers and, finally, to determine the content of phenolics and antioxidant activity. The samples of monofloral bee pollen of Elaeis guineensis L, Cocos nucifera L. e Attalea funifera Mart. were submitted to the acetolysis process for pollen analysis and solvent extraction for chemical analyses. After the acetolysis, five permanent slides were mounted and counted at least 500 pollen grains per samples. For the volumetric analysis, 25 pollen units were used as the basis for the respective measurements and volumetric estimates with the aid of spatial geometry. The chemical analyzes were obtained from the ethanolic extracts and then the AcOEt fraction by partition. In order to determine the phenolic content, the Folin-Ciocalteau test was performed and for the antioxidant activity, DPPH and ABTS+ radicals were used. In the chemical analysis, fractions of ethanolic extracts (EtOH) and acetate (AcOEt) were produced, as well as the use radical free as DPPH and ABTS+ for the antioxidant tests. It is possible to state that pollen analysis is an essential tool in the botanical identification of bee pollen samples and that the classification proposed for the beekeepers is not reliable, since they are only empirical information. The volumetric analysis, besides pollen counting, was fundamental to determine the botanical origin, since it allowed to classify the samples analyzed in mono or multifloral. Thus, among the 25 analyzed samples of E. guineensis, 21 were classified as monofloral, among 13 analyzed of C. nucifera. Only three were not classified as monofloral and among the seven analyzed samples of A. funifera, only one was not considered monofloral. In relation to the samples of C. nucifera it was possible to determine its monofloral characteristic through the pollen count, already in relation to the type A. funifera it was necessary to perform volumetric analyzes to confirm this characteristic. Finally, in relation to the chemical analysis, it can be stated that the results were relevant for the bee product, despite the low values found for the phenolic content, being 1.5 ± 0.15 at 26.3 ± 0.48 mg GAE/g in the ETOH fraction and 8.3 ± 0.87 at 125.8 ± 0.93 mg GAE/g in the AcOEt fraction compared to the literature data. Samples of Elaeis guineensis L. showed an antioxidant activity ranging from 34.9 ± 0.53 to 588.2 ± 4.65 µg / mL ± EPM in the DPPH method and from 20.8 ± 0.26 to 383, 9 ± 0.75 µg / mL ± EPM in the ABTS + method. This information can be used as a form of certification in ensuring quality and adding value to the product